A proposed program for the rehabilitation of self-confidence and its impact on the learning level of the throwing skills in Greek-Roman wrestling. - Abdullah, Asaad (Journal of Physical Education, 2012)
Section I: This section included the provided and the importance of research, the factors which effect of the levels of skills learning & the overlap between them & the importance of each factor, also touched on the importance of his research and the need for it to know the impact of the level of self-confidence level of skills learning for the throwing skills in Greek-Roman wrestling. Also included problem of the research cited by the researcher briefly was the weakness in the level of skills learning with throwing skills in Greek-Roman wrestling for students at the third stage in the College of Physical Education. Also included the goals of the research that was focused on identifying levels of self-confidence for the sample and the effect of rehabilitation of these levels to the level of skills learning to throwing skills in Greek-Roman wrestling. Also included the researcher's hypothesizes that there are differences random is not statistically significant between the results of tests of self-confidence before and after the control group, and moral statistically significant for the experimental group, and the differences random is not statistically significant between the results of the performance of the throwing skills and the average community for the group control group, and significant differences are statistically significant for the experimental group, finally the researcher seal the section areas of research that showed the sample and the place where the research work and the time period for it.Section II: This section studies the theory that the researcher, which addressed the issue of self-confidence and going on around him.Section III: In this section addressed to the researcher, the research method used to achieve the objectives and Guess, and sample tests that were applied by the proposed approach, and also the actions of the field work and a description of the research and testing the proposed approach for the rehabilitation of self-confidence and levels of statistical methods used by the researcher to address the raw results obtained from tests . Part IV: After the statistical treatment of results by the researcher, the presentation and analysis and discussion of the results of this section.Part V: In the light of the findings of the researcher of the results in section IV, n introduced by the conclusions of which were identical to the set of assumptions to solve the problem before the search, in the light of these conclusions, recommended some of the recommendations in order to give the subject of self-confidence due importance by the staff side Sports